Climate-Smart Agriculture and Climate Information Services Action for Food Systems Transformation in Ghana: Capacity strengthening and Stakeholder consultation - Tepa-Yotto, Ghislain; Tamo, Manuele; Dalaa, Mustapha Alasan; Dinku, Tufa; Obeng, Faustina; Wilson, Michael; Yeboah, Stephen; Kyere, Reginald; Tahidu, Osman; Falade, Titilayo D.O.; Martey, Francisca; Asare-Kyei, Daniel; et al. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
AICCRA Ghana Cluster in collaboration with WA Regional Cluster and national, regional and international partners convened a two-week capacity strengthening event. The format of the event was hybrid with important in-person attendance arranged. The training aligns with the clusters expected contributions to specific project targets against four AICCRA performance indicators: PDO1- CCAFS partners and stakeholders in the Project area are increasingly accessing enhanced climate information services and/or validated climate-smart agriculture technologies; IPI 2.2- Partnerships launched/ strengthened between AICCRA-funded CGIAR and NARS scientists, universities, public sector stakeholders, farmer organizations, NGOs and private sector; IPI 2.3- People engaged in AICCRA-funded capacity development activities; and IPI 3.1- Validated climate information services and climate-smart agriculture technologies disseminated / made accessible. Therefore, the training was structured around four main segments: 1) Climate-smart one-health approach and partnership launch; 2) Early Warning & Rapid Response (EWRR) for a climate-smart IPM; 3) NFCS partnership strengthening and stakeholder consultation; 4) Enhancing access to CSA/CIS bundles while addressing gender and social inclusion (GSI).